DISTORSI HADIS KHILĀFAH ‘ALĀ MINHĀJI AN-NUBUWWAH (studi kritik analisis hadis Khilāfah ‘Ala Minhāji an-Nubuwwah) - dedi herdiansyah (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2019)
July 19, 2017 Hizb ut-Tahrir Indonesia (HTI) after 37 years of this movement was present in Indonesia officially disbanded by the government after its SK Legislation was revoked. the noise occurs everywhere between the pro and the counter. what caused the government to abolish the SK of the HTI Legal Entity.? The spirit of movement is based on the argument, among which is the hadith of the return of the prophetic khilafah. This research is aimed to analyze the hadeeth of the return of the prophetic khilafah of prophethood, what is sanadnya shahih or dhaif? This research is done through a qualitative descriptive method, which is criticizing the hadeeth of either the sanad or its mathematics with various stages taken: Takhrij Hadith, I'tibar history, sanad research, material research to the conclusion whether the hadith is strong or weak. There is a critical point in the focus of this study: Jarh Imam Al-Bukhary against rawi named Habib bin Salim, The Kemenangan of the Prophet r, named Daud ibn Ibrahim, and the political part of it was during the caliph of 'Umar bin' Abdul Aziz. But in this journal the author only discusses Jarh Imam Al-Bukhary's criticism of Habib bin Salim, while the other two criticisms need further research.